2014
DOI: 10.1186/1743-0003-11-90
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of event-related desynchronization during kinematic and kinetic hand movements

Abstract: BackgroundEvent-related desynchronization/synchronization (ERD/ERS) is a relative power decrease/increase of electroencephalogram (EEG) in a specific frequency band during physical motor execution and mental motor imagery, thus it is widely used for the brain-computer interface (BCI) purpose. However what the ERD really reflects and its frequency band specific role have not been agreed and are under investigation. Understanding the underlying mechanism which causes a significant ERD would be crucial to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 23 publications
(38 reference statements)
5
70
1
Order By: Relevance
“…During self-paced movements however, ERD has been observed to precede movement onset [22, 31-33]. Pre-movement ERD has also been observed previously before cued predictable movements [16, 21], including passive movements imposed on the subject [17, 18]. This study built on these findings, showing that ERD appeared in advance of a predictable imposed movement from a robotic orthosis when the subject was instructed to remain passive.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…During self-paced movements however, ERD has been observed to precede movement onset [22, 31-33]. Pre-movement ERD has also been observed previously before cued predictable movements [16, 21], including passive movements imposed on the subject [17, 18]. This study built on these findings, showing that ERD appeared in advance of a predictable imposed movement from a robotic orthosis when the subject was instructed to remain passive.…”
Section: Discussionsupporting
confidence: 72%
“…The mean secondary synchronization was greatest in the passive subject/active robot condition, followed by the active subject/active robot condition. ERD and ERS in relation to kinematic and kinetic hand movements were recently characterized by use of a 3×4 factorial design experiment in which the subjects repeated hand grasping movements at different speeds and forces [16]. The authors found that although grasping force did not affect the magnitude or time course of ERD/ERS, repeating grasping motions caused repeated up-modulation of the signal power.…”
Section: Discussionmentioning
confidence: 99%
“…What makes this line of enquiry interesting is to investigate a link between a simple experiment task in laboratory and quality of life represented by the assessment of hand writing. In our recent work (Nakayashiki, Saeki, Takata, Hayashi, & Kondo, 2014), it was found that the ERD reflected the motor planning (speed and trajectories) rather than motor command generation therefore, we anticipate that the assessment in handwriting task would be a comprehensive marker which is correlated with the strength of ERD production.…”
Section: Discussionmentioning
confidence: 97%
“…During the motor imagery, distinct Mu/Beta event related (de)synchronization phenomena are generally present around the motor cortex, which can be used for the classification of individual intention [2], [3].…”
Section: Introductionmentioning
confidence: 99%